Ruptured Uterine Sacculation: A Rare Presentation of Ectopic Implantation - Saha, Arabinda; Bhargava, Vijay Laxmi (Acta obstetricia et gynecologica Scandinavica, 1988)
Pregnancy growing in the uterine sacculation following medical termination of pregnancy is a rare occurrence. We present one such case in which rupture occurred on the ward while the patient was waiting for diagnostic laparotomy.